Pengaruh Model Pembelajaran Cooperative Integrated Reading And Composition Berbantuan Lembar Kerja Siswa Berbasis Realistic Mathematics Education Terhadap Kemampuan Pemecahan Masalah Siswa - Triya Aryanti; Fadhilah Rahmawati; Megita Dwi Pamungkas (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2023)
The learning of mathematics is not only focused on improving students' computational skills but also prioritizes the development of problem-solving abilities. One of the approaches that can be used to enhance problem-solving skills is the CIRC learning model aided by LKS (Student Worksheets) based on RME (Realistic Mathematics Education). This research employed a quantitative method with a quasi-experimental design, specifically the nonequivalent control group design. Two classes were involved in the study: the experimental class (XI MIPA 2) and the control class (XI MIPA 4). The research instruments used were tests, interview guidelines, observation sheets, and validation sheets. Data was collected through tests, observations, interviews, documentation, and questionnaires. The hypothesis test results indicated that students' problem-solving abilities taught using the CIRC learning model aided by LKS based on RME were superior compared to those taught using the CIRC model on the topics of sequences and series. It was proven that implementing the CIRC learning model aided by LKS based on RME significantly improved problem-solving skills among students of XI MIPA 2 at SMA Negeri 2 Grabag, with a high achievement category.